2003
DOI: 10.1002/bip.10428
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence‐based methods for evaluating the RNA affinity and specificity of HIV‐1 Rev–RRE inhibitors

Abstract: RNA plays a pivotal role in the replication of all organisms, including viral and bacterial pathogens. The development of small molecules that selectively interfere with undesired RNA activity is a promising new direction for drug design. Currently, there are no anti-HIV treatments that target nucleic acids. This article presents the HIV-1 Rev response element (RRE) as an important focus for the development of antiviral agents that target RNA. The Rev binding site on the RRE is highly conserved, even between d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 52 publications
3
84
0
Order By: Relevance
“…Full-length CSP-1 protein inhibits S. pneumoniae growth at only ≥10 μM (21). The 116 residue HIV-Rev protein binds to RNA with Kd approximately 1 nM (28). Nociceptin (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) is an agonist at only nM concentrations (25).…”
Section: Discussionmentioning
confidence: 99%
“…Full-length CSP-1 protein inhibits S. pneumoniae growth at only ≥10 μM (21). The 116 residue HIV-Rev protein binds to RNA with Kd approximately 1 nM (28). Nociceptin (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) is an agonist at only nM concentrations (25).…”
Section: Discussionmentioning
confidence: 99%
“…Re-evaluating the activity of each inhibitor under such stringent conditions yields essential information regarding the ligand's selectivity (Figure 8 b). [61] As part of the assay's validation process, we demonstrated its capability to faithfully reproduce the known affinity and selectivity trends among aminoglycoside antibiotics. [60] We also illustrated the ability of this novel assembly to readily handle binders that interfere with common biophysical assays (such as fluorescence anisotropy).…”
Section: A Novel Solid-phase Assembly For Identifying Potent and Selementioning
confidence: 96%
“…Challenging the immobilized fluorescent Rev ± RRE complex with potential inhibitors and determining the amount of RevFl displaced generates the necessary information regarding a ligand's affinity (Figure 8 a). [61] The strengths of this assay are its robustness and reliable performance in the presence of large amounts of competing nucleic acids. Re-evaluating the activity of each inhibitor under such stringent conditions yields essential information regarding the ligand's selectivity (Figure 8 b).…”
Section: A Novel Solid-phase Assembly For Identifying Potent and Selementioning
confidence: 99%
“…[9] This structure revealed that only the central part of the protein (residues 9-65) is structured, while the rest is intrinsically disordered. Motivated by the important role of Rev in the HIV replication cycle, and its potential as a drug target, [11,13,14] we developed two efficient synthetic and recombinant methods that allow the production of sufficient amounts of highly pure Rev, and provide the flexibility to prepare novel synthetic analogues of Rev for future studies to elucidate its structure-function relationship with spatial and temporal control.…”
Section: Introductionmentioning
confidence: 99%